Managing Severe Malaria in the Era of Pre-elimination - Afroze, Khalisa; Sayeed, Abdullah Abu; Faiz, M Abul (Bangladesh Critical Care Journal, 2015)
Severe malaria is a medical emergency mainly caused by falciparum parasite responsible for nearly 584,000 annual deaths globally in 2013.Most deaths in malaria happens in endemic countries before the patient reaches hospitals or within short period after admission; support of Intensive Care Unit (ICU) for optimum treatment of severe malaria is not available in many endemic countries. WHO recommends confirmation of diagnosis by immunochromatographic rapid test or by blood film examination and for treatment to use artemisinin based combination treatment (ACT) for uncomplicated falciparum malaria and thus reduces the incidence of severe malaria. Treatment recommended for severe malaria is IV artesunate for at least 24 hours followed by full dose oral ACT on recovery of per os status. Early feeding in unconscious patient of severe malaria increases the possibility of aspiration pneumonia. A single dose of rectal artesunate reduces death by 25% when used at a community level as pre-referral treatment and completion of treatment follows after admission. Single dose of primaquine 0.25 mg/kg is recommended for reduction of transmission. District hospitals in high endemic area should have facility of dialysis and referral Medical College Hospital should have functional ICU for further reduction of malaria death. Bangladesh Crit Care J September 2015; 3 (2): 57-59